2002
DOI: 10.1128/jvi.76.19.9981-9990.2002
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Levels of Recent Thymic Emigrants in Peripheral Blood of Simian Immunodeficiency Virus-Infected Macaques Correlate with Alterations within the Thymus

Abstract: The thymus is responsible for de novo production of CD4؉ and CD8 ؉ T cells and therefore is essential for T-cell renewal. The goal of this study was to assess the impact of simian immunodeficiency virus (SIV) infection on the production of T cells by the thymus. Levels of recent thymic emigrants within the peripheral blood were assessed through quantification of macaque T-cell receptor excision circles (TREC). Comparison of SIVinfected macaques (n ‫؍‬ 15) to uninfected macaques (n ‫؍‬ 23) revealed stable or in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 61 publications
0
28
0
Order By: Relevance
“…76 The fact that apoptosis in the thymus as well as in the LNs of macaques infected with pathogenic SIV occurs in both infected and uninfected T cells indicates again that mechanisms other than the direct cytopathic effect of HIV are involved in this disease process. 53,77 Furthermore, studies performed in pathogenic and nonpathogenic primate models of HIV or SIV infection during the chronic asymptomatic phase have identified a correlation between the induction of enhanced in vitro T-cell apoptosis and the in vivo pathogenic nature of the retroviral infection 27,44,51,78-84 ( Figure 1b). Thus, enhanced levels of apoptosis in CD4 þ T cells were observed in HIV-1-infected human individuals, rhesus macaques infected with a pathogenic strain of SIVmac, and chimpanzees infected with a pathogenic strain of SIVcpz leading to AIDS, 78,85 while enhanced CD8 T-cell apoptosis was observed in both pathogenic and nonpathogenic primate models.…”
Section: T-cell Apoptosis and Aidsmentioning
confidence: 99%
“…76 The fact that apoptosis in the thymus as well as in the LNs of macaques infected with pathogenic SIV occurs in both infected and uninfected T cells indicates again that mechanisms other than the direct cytopathic effect of HIV are involved in this disease process. 53,77 Furthermore, studies performed in pathogenic and nonpathogenic primate models of HIV or SIV infection during the chronic asymptomatic phase have identified a correlation between the induction of enhanced in vitro T-cell apoptosis and the in vivo pathogenic nature of the retroviral infection 27,44,51,78-84 ( Figure 1b). Thus, enhanced levels of apoptosis in CD4 þ T cells were observed in HIV-1-infected human individuals, rhesus macaques infected with a pathogenic strain of SIVmac, and chimpanzees infected with a pathogenic strain of SIVcpz leading to AIDS, 78,85 while enhanced CD8 T-cell apoptosis was observed in both pathogenic and nonpathogenic primate models.…”
Section: T-cell Apoptosis and Aidsmentioning
confidence: 99%
“…TREC consist of fragments of DNA excised during rearrangement of TCR genes and hence TREC levels represent the function of the thymus. Thus, aged subjects with an atrophied thymus have a 20-fold decrease in levels of TREC compared with young subjects (22) and nonhuman primates subjected to thymectomy have a 40-fold decrease in the levels of TREC 1 year after the procedure (23,24). If the T cell compartment of recipients of cardiac transplants was restored by proliferation of residual T cells, a decrease in levels of TREC in these subjects would indicate a lack of thymic function.…”
Section: Thymic Function and Restoration Of The T Cell Compartmentmentioning
confidence: 99%
“…Furthermore, recovery of thymic function after highly active antiretroviral therapy has been correlated with immune recovery (15)(16)(17)36). Thymic sections from HIV-1-infected humans or SIV/SHIV-infected macaques show increased apoptosis, suggesting that HIV-1 can either directly or indirectly hasten thymocyte depletion (28,29,45,47,56). A number of studies addressing mechanisms of CD4 ϩ thymocyte death in the thymus organ have indicated that both direct viral lysis and bystander apoptosis occur during thymocyte depletion (5,6,30,48).…”
Section: Infection With Human Immunodeficiency Virus Type 1 (Hiv-1) Imentioning
confidence: 99%